2018
DOI: 10.1021/acsnano.8b04338
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging of Tumor-Associated Macrophages and Their Response to Therapy Using 64Cu-Labeled Macrin

Abstract: Tumor associated macrophages (TAMs) are widely implicated in cancer progression, and TAM levels can influence drug responses, particularly to immunotherapy and nanomedicines. However, it has been difficult to quantify total TAM numbers and their dynamic spatiotemporal distribution in a non-invasive and translationally relevant manner. Here, we address this need by developing a pharmacokinetically optimized, 64Cu-labeled polyglucose nanoparticle (Macrin) for quantitative positron emission tomography (PET) imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 62 publications
(157 reference statements)
4
109
1
Order By: Relevance
“…c and Supporting Information Fig. S6), where phagocytes including tumor‐associated macrophages are known to reside at high levels, especially in the HT1080 model used here . Indeed, high‐magnification images showed that most Tzm accumulated within phagocytes rather than tumor cells, regardless of HER2 expression (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…c and Supporting Information Fig. S6), where phagocytes including tumor‐associated macrophages are known to reside at high levels, especially in the HT1080 model used here . Indeed, high‐magnification images showed that most Tzm accumulated within phagocytes rather than tumor cells, regardless of HER2 expression (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…For instance, a combination of triple imaging techniques (i.e., dark‐field light microscopy, electron microscopy, and nanoscale secondary ion mass spectrometry) was used to study the NP interaction with green algae in the context of NP localization, internalization, and chemical identity . Also, quantitative imaging of co‐localization of tumor associated macrophages with therapeutic 64 Cu‐labeled polyglucose nanoparticle in an orthotopic model of lung adenocarcinoma was accomplished via PET, in vivo confocal microscopy, and tissue‐cleared LSFM . PCXI has already been applied for ex vivo and in vivo studies on mucociliary transport of large microparticles or 5–100 µm fibers in the trachea or upper airways of animal models such as mice and pigs and for monitoring the delivery of liquids to murine lungs via nose or intubated cannula delivery .…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, imaging extravascular macrophages in solid tumors required a longer circulating NP, thus a 20 nm sized Macrin was developed to maximize tissue penetration and macrophage uptake. [34] Concordantly, these NPs were labeled with Cu 64 (t ½ = 12.7 h). Materials have also been labeled for imaging with other modalities.…”
Section: In Vivo Imaging Overviewmentioning
confidence: 88%
“…Certain fluorescently tagged NPs, such as the FDA-approved, carboxymethyldextran-coated iron oxide NP ferumoxytol, and a recently developed polyglucose NP Macrin, can be injected to label phagocytes, such as macrophages and neutrophils in the mouse. [34,163,164] On the other hand, cancer cells can be labeled with recently developed telomerase-specific spherical nucleic acid probes. [165] To improve the specificity of labeling, fluorescent antibodies targeting markers expressed on the cell-types of interest can also be used.…”
Section: Injectable Reporters For Cell Identificationmentioning
confidence: 99%